EXPERIMENTAL PRESSURE SOLUTION COMPACTION OF SYNTHETIC HALITE/CALCITE AGGREGATES - Zubtsov S.; Renard F.; Gratier J.-P.; Guiguet R.; Traskine V.; Dysthe D.K. (My University, 2004)
Experimental observations are reported of weakening of sediment-like aggregates by addition of hard particles. Sieved mixtures of calcite and halite grains are experimentally compacted in drained pressure cells in the presence of a saturated aqueous solution. The individual halite grains deform easily by pressure solution creep whereas calcite grains act as hard objects and resist compaction. The fastest rate of compaction of the mixed aggregate is not obtained for a 100% halite aggregate but for a content of halite grains between 45% and 75%. We propose that this unusual compaction behavior reflects the competition between two mechanisms at the grain scale: intergranular pressure solution at grain contacts and grain boundary healing between halite grains that prevent further compaction.
Keywords: Compaction; Diagenesis; Halite; Polymineralic aggregate; Pressure solution creep